Independent Theatre in Contemporary Europe Structures Aesthetics Cultural Policy - Brauneck, Manfred; ITI Germany (transcript Verlag, 2017)
Over the past 20 years European theatre underwent fundamental changes in terms of aesthetic focus, institutional structure and in its position in society. The impetus for these changes was provided by a new generation in the independent theatre scene. This book brings together studies on the state of independent theatre in different European countries, focusing on the fields of dance and performance, children and youth theatre, theatre and migration and post-migrant theatre. Additionally, it includes essays on experimental musical theatre, and different cultural policies for independent theatre scenes in a range of European countries.
Description based on print version record.
KU Select 2016 Front List Collection
Keywords: Performing Arts / Theater / History & Criticism; Language Arts & Disciplines / Communication Studies; Performing arts; Electronic books